The Responsibility Of The Partners In Their Own Funds For The Debts And Obligations Of The Limited Liability Company - Suleiman Saleh, Elham Jihad (Opción, 2019)
The Saudi regulator in the Companies Law issued in 1437 decided that the responsibility of the partners in the limited liability company is limited to the amount of his share in the capital that he placed in this company, and this is the general principle, except that when reviewing the texts of the Saudi com- panies system, we find that the organizer has put Cases in which the partner in the limited liability company is asked about the debts and obligations of the company personal responsibility with his own money, i.e. his responsibility exceeds the amount of his share of the capital, and exceeds it to his own money, and this is what we will explain through two requirements, we talk in the first demand about the original, which is the limited responsibility of the partner in The company in charge The limited liability is limited to his share in the cap- ital, and we speak in the second request about the exception in the partner’s responsibility in the limited liability company for the debts and obligations of the company with his own funds.